"Ask me what I need": A call for shifting responsibility upwards and creating inclusive learning environments in clinical placement. (September 2020) - Epstein, I.; Stephens, L.; Severino, S. Mora; Khanlou, N.; Mack, T.; Barker, D.; Dadashi, N.
Abstract: Background: Ontario's human-rights legislation and institutions' support for students with disabilities have influenced these students' increased enrolment in the postsecondary environment. Yet more attention is paid to in-classroom than to out-of-classroom experiences. Students with disabilities enrolled in nursing are least likely to be accommodated. This has significant implications for access and equity upon graduation, as clinical placements are a bridge between school and employment. Objectives: To explore clinical instructors' and students who identify with disabilities' perspectives on nursing clinical placements. Method: A descriptive case-report was used: interactive take-home diaries were completed and semi-structured interviews were conducted with clinical instructors (n-14) and nursing students with disabilities (n-14) in Ontario. An iterative inductive analysis was undertaken. Results: Three overarching themes were identified: (a) an immovable clinical environment in relation to technology and time, (b) a perceived conflict between nursing and disability identity, and (c) a need to shift responsibility upwards while listening to lived experience. The clinical environment is a highly contested space; different identity groups have distinct roles and differing degrees of power within it. Conclusion: Our research calls for a shift in the nursing landscape to be led by education and medical institutions that can build supportive networks, develop clear policies and listen to nursing students with disabilities.